The intervention seasons of thoracic endovascular aortic repair impacted the outcomes for patients with type B aortic dissection - Zhao, Kaiwen; Zhu, Hongqiao; He, Xiaomin; Liang, Taiping; Sun, Yudong; Zhou, Jian; Jing, Zaiping (Frontiers in Cardiovascular Medicine, 2023)
Purpose The objective of this research was to investigate whether seasonal variations influence the outcomes of type B aortic dissection (TBAD) patients with thoracic endovascular aortic repair (TEVAR). Patients and methods From 2003 to 2020, a retrospective cohort study was performed, which included 1,123 TBAD patients who received TEVAR. Medical records were used to gather data on baseline characteristics. Outcomes including all-cause mortality and aortic-related adverse events (ARAEs) were tracked and analyzed. Results Of the 1,123 TBAD patients in this study, 308 received TEVAR in spring (27.4%), 240 cases in summer (21.4%), 260 cases in autumn (23.2%), and 315 cases in winter (28.0%). Patients in the autumn group had a significantly lower risk of 1-year mortality than those in the spring group (hazard ratio: 2.66, 95% confidence interval: 1.06–6.67, p = 0.037). Kaplan–Meier curves revealed that patients who underwent TEVAR in autumn had a lower risk of 30-day ARAEs (p = 0.049) and 1-year mortality (p = 0.03) than those in spring. Conclusion This study confirmed that TEVAR operated in autumn for TBAD was associated with a lower risk of 30-day ARAEs and 1-year mortality than in spring.